A novel energy efficient powered ankle prosthesis using four-bar controlled compliant actuator. (December 2018) - Sahoo, Saikat; Pratihar, Dilip Kumar; Mukhopadhyay, Sudipta
A powered ankle prosthesis has the ability to replace a biological ankle, also it can remove the difficulties faced due to the usage of passive ankle prosthesis. However, the energy consumption of the set-up, weight and portability of the motor, and its electronics are still the issues to be addressed. This study is solely focused on the reduction of power consumption of the motor during the stance phase of locomotion. Thus, a compliant actuator controlled by the four-bar mechanism with a special rocker arrangement is proposed, which eventually can reduce the power consumption by a significant amount. The reduction of power consumption not only expands the run time, but also reduces the weight and cost of the prosthesis indirectly. An optimization problem is also formulated to optimize the links' lengths and spring stiffness in order to mimic the behavior of a normal ankle joint and solved using a genetic algorithm. Finally, the analytical and simulation results of the proposed model in terms of energy consumption and required peak motor power are compared with that of some renowned powered ankle prosthesis developed using the widely used screw transmission mechanism, a popular compliance actuation technique and an existing four-bar mechanism.